An integrated understanding of librarian professional identity. Issue 4 (31st May 2019) - Pierson, Cameron M.; Goulding, Anne; Campbell-Meier, Jennifer
Abstract : Purpose: The purpose of this paper is to review literature on librarian professional identity to develop a more integrated understanding of this topic. Design/methodology/approach: Literature was retrieved and analysed with no date or geographic limit from nine databases on the subject of librarian professional identity. A combination of keywords and database specific controlled language was utilized to increase retrieval, as well as inspection of reference lists. Exclusion criteria were applied. Findings: The review found 14 characteristics or themes relevant to librarian professional identity formation and development, understood as process over time. This process is in part defined by benchmark events, such as critical incidents, as well as highly personal aspects, such as perception of these incidents. This review also introduces an original conceptual model of librarian professional identity formation and development. Research limitations/implications: A limitation of this review was that only English-language literature was considered. A further limitation is the omission of works that have not been formally published. Additionally, the model introduced is untested. Originality/value: By reviewing librarian professional identity literature, this paper offers an integrated understanding of this topic and introduces a new, original model to understand the process of librarian professional identity and development. It further offers an examination based on a sociological lens to examine this identity.